Psychometric Properties for Jordanian version of the Young Mania Rating Scale (YMRS) - Awakleh, Moamen Ali; Al-Emad, Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2024)
The aim of this study was to translate the Young Mania Rating Scale (YMRS) into Arabic and to revealing its psychometric properties in a sample of the Jordanian population. The study sample consisted of (150) participants, divided into two Sample: a clinical sample (89) diagnosed with bipolar disorder during a manic or hypomanic episode, and a non-clinical sample (61).To answer the study questions, several statistical analyses were conducted. The validity of the scale was examined in several ways, including: construct validity by internal consistency was assessed using Pearson's correlation coefficient between the total score and each item, which ranged between (-0.46, 0.88). This indicates high validity internal consistency. validity, and Discriminant validity was assessed by comparing the performance of the clinical and non-clinical sample using the independent samples t-test reached (7.7), This indicates that the scale was able to distinguish well between the two sample at a significance level of (0.01). The reliability of the scale was also examined in two ways: the first was to find the reliability coefficient using the internal consistency method, according to Cronbach's alpha coefficient, which reached (.87) for the clinical sample and (.81) for the non-clinical sample. The second method was to use the test-retest reliability method, where Pearson's correlation coefficient reached (0.89**).In conclusion, the results of this study suggest that the Young Mania Rating Scale has high psychometric properties in the Jordanian environment. Based on the results, the study recommends using the scale for research and clinical purposes in the Jordanian environment.
Keywords: Bipolar disorder; Clinical; Reliability; Psychometric properties; Validity; Young Mania Rating Scale (YMRS)